Intrinsic optical conductivity of a C2v symmetric topological insulator. (27th June 2017) - Sengupta, Parijat; Matsubara, Masahiko; Bellotti, Enrico; Shi, Junxia
Abstract: In this work we analytically investigate the longitudinal optical conductivity of the C 2 v symmetric topological insulator. The conductivity expressions at T  = 0 are derived using the Kubo formula and expressed as a function of the ratio of the Dresselhaus and Rashba parameters that characterize the low-energy Hamiltonian. We find that the longitudinal inter-band conductivity vanishes when Dresselhaus and Rashba parameters are equal in strength, also called the persistent spin helix state. The calculations are extended to obtain the frequency-dependent real and imaginary components of the optical conductivity for the topological Kondo insulator SmB6 which exhibits C 2 v symmetric and anisotropic Dirac cones hosting topological states at X ̄ point on the surface Brillouin zone.